Effect of industrial processing of crackers on the recovery and quantitation of allergens with ELISA kits - Hidalgo-Víquez, Cindy (2024)
Introduction. Processing foods may generate limitations on the recovery and quantitation of allergens. Factors such as geometry or thermal treatment can influence the veracity of the assay results. Objective. To determine the effect of processing on the recovery and quantification of allergens. Materials and methods. Study conducted in Costa Rica between 2020 and 2021 in the Compañía de galletas Pozuelo DCR. S.A. The geometry was evaluated with two cracker molds (traditional and XL). The effect of baking was evaluated with the traditional cracker type. For both experiments, samples were taken from four batches, and they were analyzed with three different kits for milk and egg analysis in an independent way. Results. The effect of geometry was observed for recovery and quantitation of egg residues was significantly affected by cracker geometry (P= 0.0228) compared to milk (P= 0.4335), regardless of the analytical kit used. The post baking decrease of quantitation effect was presented equally regardless of the kit used (P=0.4245) on egg. Very poor recovery of egg residues (4-5 %) was observed after cracker baking. For milk allergens, there was not a significant difference on the quantitation and recovery after baking among kits (P=0.1682), which is due to the variability of the data among kits. Conclusions. Processing reduces the efficacy of kits to detect the real quantity of allergens in foods. The analytical kit must be evaluated with the matrix to be analyzed, to determine how much impact the processing can have on the quantitation of allergens.